The top ten cloud-security practices in next-generation networking. (1st January 2012) - Halton, Wolf Michael; Rahman, Syed
Next-generation networking is moving out of the LAN and adopting cloud computing increasingly. Virtual machines and clouds mask the hardware infrastructure from the LAN administrator as well. Cloud architecture will be ubiquitous and in the future clouds will drop the unnecessary distinction of platform as a service, leaving a slightly larger infrastructure as a service (IaaS) level and an application level (SaaS). Provisioning costs will get lower but the costs of data breaches will continue to climb. This paper explores the security ramifications of cloud-adoption by reviewing the literature and presenting a collection of best-practices for security in the cloud.